2016
DOI: 10.1016/j.atherosclerosis.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A loss-of-function variant in OSBPL1A predisposes to low plasma HDL cholesterol levels and impaired cholesterol efflux capacity

Abstract: The present work represents the first characterization of a human OSBPL1A mutation. Our observations provide evidence that a familial loss-of-function mutation in OSBPL1A affects the first step of the reverse cholesterol transport process and associates with a low HDL-C phenotype. This suggests that rare mutations in OSBPL genes may contribute to dyslipidemias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Dyslipidaemia can predispose individuals to cardiovascular disease, hepatic disease and metabolic syndrome(102). Genetic analyses of patients with dyslipidaemia have indicated a role for the OSBP/OSBPL/ORP family in lipoprotein metabolism and this suggestion has been supported by functional studies in both mouse models and cell culture studies(103).Individuals who possess a heterozygous loss-of-function mutation in ORP1L have extremely low plasma levels of HDL cholesterol and apolipoprotein A1 (apoA-1)(103). In vitro assays demonstrated that fibroblasts carrying the loss of function mutation had significantly reduced cholesterol efflux to lipid free apoA1, but not to mature HDL particles, which suggests a defect in the ATP binding cassette transporter A1 (ABCA1) efflux pathway.…”
mentioning
confidence: 99%
“…Dyslipidaemia can predispose individuals to cardiovascular disease, hepatic disease and metabolic syndrome(102). Genetic analyses of patients with dyslipidaemia have indicated a role for the OSBP/OSBPL/ORP family in lipoprotein metabolism and this suggestion has been supported by functional studies in both mouse models and cell culture studies(103).Individuals who possess a heterozygous loss-of-function mutation in ORP1L have extremely low plasma levels of HDL cholesterol and apolipoprotein A1 (apoA-1)(103). In vitro assays demonstrated that fibroblasts carrying the loss of function mutation had significantly reduced cholesterol efflux to lipid free apoA1, but not to mature HDL particles, which suggests a defect in the ATP binding cassette transporter A1 (ABCA1) efflux pathway.…”
mentioning
confidence: 99%
“…In addition, other OMIM genes included in the deletions have also been shown to be associated with specific phenotypes. Heterozygous loss of function variants of OSBPL1A are associated with low plasma high density lipoprotein cholesterol levels and impaired cholesterol efflux capacity (Motazacker et al, ), therefore our patient 1 may benefit from a lipid profile screening. Of note, there is a hemizygosity of ZNF24 in patient 2, which is associated with seizures and tremors (Cody et al, ), but these features are not seen in our patient.…”
Section: Discussionmentioning
confidence: 93%
“…The gene Osbpl9 ( oxysterol binding protein-like 9 ) belongs to the oxysterol-binding protein family, which has been implicated in the function of, e.g., endoplasmic reticulum (ER) junctions, non-vesicular transport of lipids, integration of sterol and sphingomyelin metabolism, sterol transport, regulation of neutral lipid metabolism, and regulation of signaling cascades ( Olkkonen et al, 2006 ). Familial loss-of-function variants of OSBPL1 in humans predisposed to impaired reverse cholesterol transport and low plasma high-density lipoprotein (HDL) levels ( Motazacker et al, 2016 ). Studies on OSBPL10 suggested a suppressive function on hepatic lipogenesis and very low density lipoprotein (VLDL) production ( Perttilä et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%